Ultrasonic-vibration-assisted reflow machining of ceramic gels - Junyan Mao; Shunzo Shimai; Haohao Ji; Jian Zhang; Xiaojian Mao; Shiwei Wang (Journal of Advanced Ceramics)
This paper presents a novel ultrasonic vibration-assisted machining method for ceramic gels (wet green bodies), aiming to overcome the limitations of conventional ceramic machining methods, which often cause defects such as chipping and cracking owing to the low strength of dried green bodies and the brittleness of pre-sintered and sintered ceramics. Additionally, they struggle to produce ceramics with special shapes, non-communicating slots and holes. The proposed method leverages the shear-stress-induced reflow property of ceramic gel by applying high-frequency ultrasonic vibration in the vertical direction to selectively remove the undesired part of the ceramic gel. This approach enables precise, non-destructive processing for surface modification, slotting, and drilling, achieving feature sizes on the order of microns. The experimental results further demonstrate its effectiveness in bonding ceramic components. This method offers a promising alternative to conventional ceramic machining methods for advanced ceramic manufacturing.